Analisis Kemampuan Profesional Dan Independensi Auditor Internal Terhadap Kualitas Laporan Audit Pada PDAM Tirta Pakuan Kota Bogor - Triandi, Triandi; Fahmi, Arief; Putri, Nindha Hafidza (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
This study aims to determine the professional ability, the intemal auditor independence and audit quality reports as well as to analyze the influence of professional ability and independence of intemal auditors on the quality of the audit report. The research method used was a qualitative and quantitative methods. To answer the research hypotheses using multiple regression analysis, after previous classical assumption testing program with the help of SPSS 22. The results showed that the overall professional capabilities included in both criteria, but on indicators in implementing the tasks are constrained by the management as well as biowledge ofengagementfindings of irregularities still in suficient criteria. Internal auditor independence variables included in both categories. While the variable quality of the audit repon is included in the excellent category. In testing normality obtained Asymp value. Sig of 0.200, interpret test data has a nonnal distribution. In testing multicollinearity tolerance value obtained at X1 and X2 at 0.321, X1 and X2 VIF value of3.115, indicating that there is no multicollinearity in the data. In heteroscedasticity test indicates heteroscedasticity does not occur because of the graph dots spread randomly. By hypothesis testing using multiple linear regression analysis showed the regression coeficientsfor the variables X1 of 0.460 and 0.553 for X2 variables, showed that every capability professional intemal auditors (X1) of one unit will lead to increased quality of audit reports (Y) equal to 0.460 and any independence internal auditors (X2) of one unit will lead to increased quality of audit reports (Y) equal to 0.553. To the value of the correlation coeficient (R) obtained a value of 0.966, indicating that there is a strong relationship between the ability of professional internal auditor, internal auditor independence and audit quality reports. Simultaneously (together), the internal auditor's professional ability and independence of intemal auditors have a significant effect on the quality ofthe audit report. Keywords: Professional ability, Independence, and Quality Audit Report.